Investigating the Utility of Leukocyte Sialic Acid Measurements in Lysosomal Free Sialic Acid Storage Disorder - Marya S. Sabir; Laura Pollard; Lynne Wolfe; David R. Adams; Carla Ciccone; Petcharat Leoyklang; Frances M. Platt; Marjan Huizing; William A. Gahl; May Christine V. Malicdan (JIMD Reports)
ABSTRACT Lysosomal free sialic acid storage disorder (FSASD) is a rare, multisystem neurodegenerative disease caused by biallelic pathogenic variants in SLC17A5, encoding sialin. FSASD is characterized by aberrant accumulation of unconjugated “free” sialic acid (Neu5Ac) within lysosomes. Depending on the specific genetic variants, affected individuals may present with either a rapidly fatal disease or progressive neurodegeneration. While skin fibroblasts have traditionally been used for diagnosis and research, the use of leukocytes in FSASD remains underexplored. This study examined Neu5Ac levels in leukocytes from three individuals with FSASD carrying distinct SLC17A5 variants. The levels in affected individuals were compared to three different groups: (1) the unaffected biological parents of each case; (2) subjects for whom 14 distinct lysosomal storage disorders (LSDs) were excluded based on enzyme analysis (n = 11); and (3) participants with a confirmed LSD diagnosis, as determined by enzyme analysis (n = 9). Individuals with FSASD exhibited significantly higher levels of free Neu5Ac compared to their unaffected biological parents (36‐fold), LSD‐negative subjects (22‐fold), and individuals with other LSDs (49‐fold). Although total Neu5Ac levels showed a non‐significant trend toward an increase in FSASD (1.3‐fold), this was primarily due to elevated free Neu5Ac, as bound Neu5Ac was slightly decreased in the leukocytes of FSASD cases relative to their unaffected parents. Overall, these findings highlight leukocytes as a valuable, minimally invasive cellular model for FSASD, offering an alternative, reliable diagnostic tool and a potential platform for monitoring therapeutic responses in future intervention trials.